Ensino de estatística através da metodologia de resolução de problemas: uma proposta aplicada ao ensino médio - Binotto, Charlote de Oliveira (2019)
The main objective of this work was to identify what contributions the Problem Solving methodology can bring to the teaching of statistical concepts in the third year of high school, as well as to elaborate, implement and analyze a methodological referral for the teaching of such concepts. In this research, we used the adaptation proposed by Mello (2018) that groups these nine steps into five steps. In this research, as in most research in mathematics education, qualitative research will be used. A questionnaire will be applied to the students of the third year of high school of the State School Presidente Castelo Branco to profile them, contributing to an a priori study on some topics of interest. The data collected were analyzed through the triangulation of methods: student annotations, theoretical framework and researcher teacher annotations. Dissertations that have already addressed the teaching of Statistics linked to the Problem Solving methodology will be reported, which will be addressed throughout the text. The methodology proved to be effective with regard to Teaching-Learning-Assessment, and the acceptance by students was satisfactory. In this methodology, the teacher ceases to be the main character -the one who teaches - to become a mediator, a questioner, that is, one who instigates and awakens to investigation, to reasoning.